Stabilization and Structural Reform in Czechoslovakia : An Assessment of the First Stage - Aghevli, Bijan (IMF Working Papers; Working Paper, 1992)
This paper analyzes the Czechoslovak reform program which was launched on January 1, 1991. Under this program, Czechoslovakia has taken decisive steps to establish a market economy, while achieving price stability and a viable external position through restrictive financial policies. But there has been a sharp decline in output. The eventual output recovery is predicated on completing structural market reforms, such as the development of financial markets and the safeguard of their stability, privatization of large enterprises, minimizing government interference with economic signals, and the imposition of the 'hard' budget constraint.